Relationship Between Implementation of Risk Analysis (Risk Assessment) and Reducing Patient Safety Incidents in Inpatient Installations) - Ritonga, Ahmad Hafizullah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patient safety is a crucial indicator of healthcare service quality. In Indonesia, inpatient units are among the most vulnerable areas for patient safety incidents due to the complexity of medical procedures and prolonged patient contact. Risk assessment plays a key role in minimizing adverse events by identifying potential hazards, evaluating risk levels, and implementing preventive measures. This study aims to analyze the relationship between the implementation of risk assessment and the reduction of patient safety incidents in the inpatient department of RSU Sembiring Delitua. A cross-sectional quantitative study was conducted in April–June 2025, involving 50 healthcare workers selected through total sampling. Data were collected using validated questionnaires and secondary data from the hospital's Patient Safety Committee. Univariate and bivariate analyses (Chi-Square test) were used. The results showed that 76% of respondents routinely identified risks, 70% actively reported incidents, and 66% followed up on assessments. Incident data from 2023 to 2024 showed a 43.75% reduction in total incidents, particularly medication errors and patient falls. The Chi-Square test revealed a significant relationship between risk assessment and the incidence of patient safety events (p = 0.018). The study concludes that effective risk assessment significantly contributes to reducing patient safety incidents. This finding emphasizes the need for continuous risk management practices, strong institutional support, and the cultivation of a safety culture across all levels of hospital services.